Perceptions of useful teaching methods and activities: a comparative study between faculty and international undergraduate non-native English speaking (NNES) students - Everley, Rebecca (Kansas State University, 2019)
This quantitative study surveyed both the faculty and international undergraduate non-native English speaking (NNES) undergraduate students to see what they perceived as being useful to the students’ learning. This research was done at Kansas State University (K-State), which is Midwestern land grant university. The research consisted of two surveys, one for faculty teaching undergraduate students and one for international undergraduate NNES students. The survey instruments were created by the researcher based on literature about teaching NNES students, first year college students, and student-centered teaching practices. The survey asked the participants to choose how useful they perceived different activities to be on a scale ranging from one (extremely useful) to five (not at all useful). The survey items on the two surveys mirrored one another, so that the results could be compared. The researcher collected and analyzed the data from the surveys. The data was first analyzed to find the descriptive statistics for each data set. The mean for each of the six variables (the need for explicit instruction, the prevention of plagiarism, the use of visual aids, the usefulness of in-class activities, the usefulness of out-of-class activities, and the use of linguistic modifications) was calculated, as well as the mean for each item. For all the variables, the student mean scores were lower than faculty mean scores, indicating that the student participants perceived the survey items as more useful than faculty did. Each item pair was analyzed using a t-tests to see if any item had a statistically significance difference, using p < .05. There were 36 pairs and 24 pairs were found to be statistically significant.
Keywords: College teaching; English as a second language; Foreign students (in U.S.)